2020
DOI: 10.1055/s-0040-1721114
|View full text |Cite
|
Sign up to set email alerts
|

Palatomaxillary Obturation and Facial Prosthetics in Head and Neck Reconstruction

Abstract: Rehabilitation of head and neck defects following trauma, oncologic resection, or congenital malformation is a challenging task. Not only is the restoration of three-dimensional form necessary for acceptable cosmesis, but simultaneous restoration of functional speech and swallow is also essential for optimal reconstruction outcomes. While advances in free tissue transfer have allowed surgical reconstruction of head and neck defects once considered inoperable and associated with poor quality of life, not all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Nasal, orbital, auricular, and upper lip prostheses have been shown to provide adequate cosmetic and functional results for patients 88,89 . A study that compared pretreatment and posttreatment quality of life for 82 patients with facial prostheses found that implant-retained prostheses were associated with significantly increased patient quality of life 90 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal, orbital, auricular, and upper lip prostheses have been shown to provide adequate cosmetic and functional results for patients 88,89 . A study that compared pretreatment and posttreatment quality of life for 82 patients with facial prostheses found that implant-retained prostheses were associated with significantly increased patient quality of life 90 .…”
Section: Resultsmentioning
confidence: 99%
“…87 Functional Outcomes -Face Nasal, orbital, auricular, and upper lip prostheses have been shown to provide adequate cosmetic and functional results for patients. 88,89 A study that compared pretreatment and posttreatment quality of life for 82 patients with facial prostheses found that implant-retained prostheses were associated with significantly increased patient quality of life. 90 A recent Dutch study looking at the long-term (14 years) quality of life for patients with facial prostheses showed high satisfaction scores with regard to comfort, color, and anatomic fit and form.…”
Section: Cost Analysis Associated Complications Functional Outcomementioning
confidence: 99%
“…The surgical reconstruction of ear 14 and nose 15 defects also presents unique challenges. Successfully addressing defects of these features by accurately replicating their intricate three‐dimensional geometry requires complex surgical techniques and the availability of appropriate donor tissues 16,17 …”
mentioning
confidence: 99%
“…Successfully addressing defects of these features by accurately replicating their intricate three-dimensional geometry requires complex surgical techniques and the availability of appropriate donor tissues. 16,17 Over the past two decades, facial transplantation has emerged as an effective treatment for patients burdened with extensive facial disfigurement, particularly when autologous strategies fail to restore optimal facial form and function. This approach, however, is still not widely performed and has stringent criteria to be met before consideration.…”
mentioning
confidence: 99%